Effect of aerosol concentration on post-corona unipolar diffusion charging: Ion density retro-controlled by aerosol space charge versus geometry of ion-aerosol mixing. Issue 2 (24th December 2021) - Jidenko, N.; Bouarouri, A.; Borra, J.-P.
Abstract: The influence of aerosol concentration on the charge per particle is investigated in post-DC corona diffusion chargers for particle diameter between 10 nm and 1 µm. Particles are charged as they pass through the charger volume by collection of ions; the ion concentration decreases along the same path due to unipolar space charge repulsion and collection on walls. With crossflow of ions and aerosols, the final mean charge per particle decreases by up to one order of magnitude with increasing aerosol concentration from 10 9 to 10 11 m −3 . The evolution of the ion density profile along particle trajectories with aerosol concentration is shown to be due to the consumption of ions by aerosol charging and to ion dispersion by unipolar space charge repulsion including ions and charged particles. Both are investigated using a simplified 1.5 D model with axial symmetry and homogeneous mixing of ions and aerosols. It is shown that, for a given operating condition, the aerosol space charge is responsible for the modification of the spatial ion distribution and the related lower Ni × τ and charge per particle reported at higher aerosol concentration. From calculations, we define the maximal aerosol concentration to keep the mean charge per particle unaffected by aerosol space charge in the optimal case of homogeneous mixing of ion and aerosol. Finally, the comparison of different ion-aerosol mixing conditions highlights that an axial symmetry of the charger reduces the influence of aerosol space charge. This effect of aerosol concentration on the particle charge is critical for aerosol chargers devoted to electric mobility selection for size measurements or focused electro-deposition, as well as for concentration measurements as performed using emerging low cost sensors based on corona chargers. Copyright © 2021 American Association for Aerosol Research